Design and Synthesis of Novel Derivatives of 4-(6-(4-Substituted Phenyl)-7H-[1,2,4] Triazolo[3,4-b][1,3,4]Thiadiazin-3- yl) Phenol as a Potent Inhibitor of Tubulin with Antitumor Activity - Kubba, Ammar A. Razzak Mahmood; Shihab, Wurood Ahmed; Al-Shawi, Nada Naji; Jabir, Majid Shamki (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
A new series of 4-(6-(4-substituted phenyl)-7H[1,2,4] triazolo[3,4b][1,3,4]thiadiazin-3-yl) phenol was synthesized and explored for anti-tubulin activity using in silico and in vitro assay models. The starting nucleus, ethyl-4-hydroxybenzoate was treated with hydrazine hydrated, and converted to 4-hydroxybenzohydrazide (1). Then, (1) was stirred with CS2 and KOH in dry EtOH to afford 2-(4-. hydroxyl benzoyl)hydrazine-1-carbodithioate, as a potassium salt (2). Compound (2) was used directly and refluxed with hydrazine hydrate to yield a parent nucleus, 4-(4-amino-5-mercapto-4H-1,2,4-triazol-3-yl)phenol (3). The target compounds (4-7), were synthesized by refluxing compound (3) with various substituted phenacyl bromides using sodium acetate as a abase, The new compounds (3-7) were characterized using different spectroscopic analysis techniques including IR, and 1HNMR. The anticipated modes of binding to α- tubulin were also investigated by means of a molecular docking experiment. The binding mode revealed good agreement with the in vitro work with binding energies of (-38.77 and -37.50 kcal/ mol) for the most potent compounds 7 and 4, respectively. The effect of synthetic novel compounds on cancer cell lines proliferation was screened by MTT assay. The ability of the synthetic compounds to induce apoptosis process was tested using acridine orange/ ethidium bromide staining. The synthetic novel compounds exhibited potent inhibitory effects on the growth and viability of cancer cell lines SKOV-3 and AMJ-13 cells. They inhibited the proliferation and growth of cancer cell lines at low concentrations, with IC50 values ranging from10.44 to 19.67 µg/mL against SKOV-3 cells, and for AMJ-13 cells, the IC50 values were11.35 to 20.52 µg/mL. The effect of the synthetic compounds on the cell growth, and proliferation of cancer cell lines was associated with increased apoptosis.Our results demonstrated that the target compounds inhibited cancer cell lines proliferation, with a mechanism of action parallel to that of other tubulin inhibitors